Gene expression profiling identifies emerging oncogenic pathways operating in extranodal NK/T-cell lymphoma, nasal type - Huang, Yenlin; de Reyniès, Aurélien; de Leval, Laurence; Ghazi, Bouchra; Martin-Garcia, Nadine; Travert, Marion; Bosq, Jacques; Brière, Josette; Petit, Barbara; Thomas, Emilie; Coppo, Paul; Marafioti, Teresa; et al. (Blood, 2010)
Biopsies and cell lines of natural killer/T-cell lymphoma, nasal type (NKTCL) were subject to combined gene expression profiling and array-based comparative genomic hybridization analyses. Compared with peripheral T-cell lymphoma, not otherwise specified, NKTCL had greater transcript levels for NK-cell and cytotoxic molecules, especially granzyme H. Compared with normal NKcells, tumors were closer to activated than resting cells and overexpressed several genes related to vascular biology, Epstein-Barr Virus–induced genes, and PDGFRA. Notably, platelet-derived growth factor receptor α and its phosphorylated form were confirmed at the protein level, and in vitro the MEC04 NKTCL cell line was sensitive to imatinib. Deregulation of the AKT, Janus kinase–signal transducers and activators of transcription, and nuclear factor-κB pathways was corroborated by nuclear expression of phosphorylated AKT, signal transducers and activators of transcription 3, and RelA in NKTCL, and several deregulated genes in these pathways mapped to regions of recurrent copy number aberrations (AKT3 [1q44], IL6R [1q21.3], CCL2 [17q12], TNFRSF21 [6p12.3]). Several features of NKTCL uncovered by this analysis suggest perturbation of angiogenic pathways. Integrative analysis also evidenced deregulation of the tumor suppressor HACE1 in the frequently deleted 6q21 region. This study highlights emerging oncogenic pathways in NKTCL and identifies novel diagnostic and therapeutic targets.